A História Negra nos Estados Unidos e no Brasil (Tempo e Argumento, 2025)
Black History, emerged as scholarship in the United States in the second half of the 19th century, gaining recognition in the following century. In Brazil, historiography on the Afro-Brazilian experience has developed since the 20th century, establishing an intellectual foundation that, at the same time, meets the demands of the context and engages with foreign production. This article aims to report and analyze the emergence and consolidation of Black History in the United States, as well as to discuss how, in Brazil, historical writing has addressed the Black experience during the period of slavery and post-Abolition, posing the question: Has Brazil formulated prescriptions for Black History? If so, find out whether the one here resembles the American paradigm.
Keywords: history; black population; black studies; race relations; race